If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -27 = -7w + 4(w + -6) Reorder the terms: -27 = -7w + 4(-6 + w) -27 = -7w + (-6 * 4 + w * 4) -27 = -7w + (-24 + 4w) Reorder the terms: -27 = -24 + -7w + 4w Combine like terms: -7w + 4w = -3w -27 = -24 + -3w Solving -27 = -24 + -3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '3w' to each side of the equation. -27 + 3w = -24 + -3w + 3w Combine like terms: -3w + 3w = 0 -27 + 3w = -24 + 0 -27 + 3w = -24 Add '27' to each side of the equation. -27 + 27 + 3w = -24 + 27 Combine like terms: -27 + 27 = 0 0 + 3w = -24 + 27 3w = -24 + 27 Combine like terms: -24 + 27 = 3 3w = 3 Divide each side by '3'. w = 1 Simplifying w = 1
| 4y^2-8y+9=0 | | 14-(5x-6)=-6(x+1)-5 | | (x+1)(x-3)=4 | | [x]=7 | | 4(2x+3)=6(x+3) | | 8=2v+6 | | .5(1-2.5y)+1.25y=.5 | | -17=n/4-13 | | .8(3v-2w)+.2(7v-2w)= | | 3y=7+5 | | -9y-3=-8y-7 | | 11x+8=4x-6 | | 5w^2+41w+42=0 | | n+15=30 | | 8+13=-3(7x-7) | | 5(5t-2)=-36 | | 9x+1=46 | | -4(y-3)=6y-7 | | m/6=-9 | | .5x+1.25y=.5 | | n+15=23 | | 8+13=3(7x-7) | | -(3x-5y)-8(2x+y)= | | -2.35+6.75=-2.18 | | (a^3b)(ab^3)= | | 0.667(6x-15)=0.75(8x+12) | | 5r-13-6r=3(r+5)-16 | | x+15=0 | | -3(4+h)+3h=9-6(h+7) | | 0.12x+1.6=0.66 | | 7x-2(x+3)=4 | | 230-2x=43x+15 |